Analysis Of Indonesia'S Pro Poor Growth Index And Poverty Equivalent Growth Rate 2017-2022 - Kartini, Kartini; Putri, Ferica Christinawati; Irna, Rizky Agusriyanti; Pratiwi, Sulistya Rini; Rahmawati, Meylin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to analyze whether Indonesia is included in the pro poor, trickle down, or anti pro poor growth. The population of this study is all provinces in Indonesia in 2017-2022. Data collection techniques used are documentation and observation, in addition to the use of secondary data to answer research questions. The analytical tool used in this study is statistical analysis using the Pro Poor Growth Index (PPGI) and Poverty Equivalent Growth Rate (PEGR) methods. The results of this study indicate that Indonesia is classified as pro-poor growth where the benefits of growth are greater for the poor than non-poor people so that growth can help reduce poverty in Indonesia.